2021
DOI: 10.15252/emmm.202114599
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal neuronal WWOX gene therapy rescues Wwox null phenotypes

Abstract: WW domain-containing oxidoreductase (WWOX) is an emerging neural gene-regulating homeostasis of the central nervous system. Germline biallelic mutations in WWOX cause WWOX-related epileptic encephalopathy (WOREE) syndrome and spinocerebellar ataxia and autosomal recessive 12 (SCAR12), two devastating neurodevelopmental disorders with highly heterogenous clinical outcomes, the most common being severe epileptic encephalopathy and profound global developmental delay. We recently demonstrated that neuronal ablati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…Due to its genomic localization, WWOX tumor suppressor activity is much more frequently impaired by the loss of heterozygosity or homozygous deletion than by point mutations [ 37 , 38 , 39 ]. Initially recognized as a putative tumor suppressor in breast cancer, the WWOX gene is now in the spotlight for its possible role in, e.g., central nervous system (CNS) and related neurological disorders [ 2 , 9 , 32 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] such as WWOX -related epileptic encephalopathy (WOREE), for which a WWOX gene therapy was recently suggested as a proof-of-concept [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its genomic localization, WWOX tumor suppressor activity is much more frequently impaired by the loss of heterozygosity or homozygous deletion than by point mutations [ 37 , 38 , 39 ]. Initially recognized as a putative tumor suppressor in breast cancer, the WWOX gene is now in the spotlight for its possible role in, e.g., central nervous system (CNS) and related neurological disorders [ 2 , 9 , 32 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] such as WWOX -related epileptic encephalopathy (WOREE), for which a WWOX gene therapy was recently suggested as a proof-of-concept [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific neuronal restoration of WWOX expression by injecting adeno‐associated virus (AAV) vector in the brain of Wwox ‐null mice rescued brain hyperexcitability, seizures, premature lethality, and behavioral deficits. These findings provide a proof‐of‐concept for WWOX gene therapy as a promising approach to treat children with WOREE (Repudi et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…Wwox knock‐out mice recapitulate the neurological phenotypes of patients with WOREE: spontaneous seizures at ∼2 weeks of age, severe hypomyelination in both the peripheral nervous system and the brain, atrophy of the optic tract, and a short lifespan of only 3–4 weeks (Cheng et al, 2020; Mallaret et al, 2014). Studies performed in a Wwox knockout mouse model demonstrated spontaneous bursting activity in the neocortex which indicated that WWOX plays a fundamental role in balancing neocortical excitability (Breton et al, 2021; Repudi et al, 2021). Specific neuronal restoration of WWOX expression by injecting adeno‐associated virus (AAV) vector in the brain of Wwox ‐null mice rescued brain hyperexcitability, seizures, premature lethality, and behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Wwox -null mutated mice were predisposed to brain hyperexcitability, intractable epilepsy, ataxia and postnatal lethality [ 183 ]. The restoration of Wwox expression by neonatal gene therapy using an adenoviral vector carrying Wwox cDNA under the control of the synapsin I gene promoter reduced premature mortality and predisposition to AE, as well as promoting partial normalization of the development of Wwox -mutated mice [ 187 ].…”
Section: Different Models Of Audiogenic Epilepsy In Rodentsmentioning
confidence: 99%